EFEKTIVITAS DAYA TARIK ENDORSEMENT PRODUK ASUS MELALUI VIDEO "UNBOXING LAPTOP 25.000.000" PLATFORM YOUTUBE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ASUS - Fakhri Ilyasa, - (2019)
This study aims to determine the effectivity of ASUS Product's Endorsement Attraction Via Youtube Video "UNBOXING LAPTOP 25.000.000" Towards ASUS's Consumer Buying Decision. The relevant concept used in this study is endorsement attraction, and consumer buying decision. While theory used in this study is the theory of consumer's information environment. This study uses a quantitative research approach. The research method used is survey. The population in this study were inhabitant of sub-district Cilandak, South Jakarta with a sample of 100 person, spread among 5 area's in Cilandak sub-district. The sampling technique in this study uses a Non-Probability Sampling with saturated samples. The technique of analyzing the effect of variable X on the Y variable using the coefficient of determination test. Data testing techniques are processed using the SPSS program (Statistical Product and Service Solution) version 16. The results of this study indicate that the correlation of variables X and Y is 0,700. Based on the results of the calculation of the coefficient of determination, the result of the influence of variable X on variable Y is 49%. Thus the calculation of t count> t table is 10,480 > 1,66055, it can be concluded that H0 is rejected and Ha accepted. Which means, endorsement attraction of ASUS Product's via Youtube video "UNBOXING LAPTOP 25.000.000" is effective to influencen ASUS consumer buying decision